2018
DOI: 10.1039/c8ra00861b
|View full text |Cite
|
Sign up to set email alerts
|

Metallic VO2 monolayer as an anode material for Li, Na, K, Mg or Ca ion storage: a first-principle study

Abstract: Using density functional theory (DFT), we assess the suitability of monolayer VO 2 as promising electrode materials for Li, Na, K, Mg and Ca ion batteries. The metallic VO 2 monolayer can offer an intrinsic advantage for the transportation of electrons in materials. The results suggest that VO 2 can provide excellent mobility with lower diffusion barriers of 0.043 eV for K, 0.119 eV for Li, 0.098 eV for Na, 0.517 eV for Mg, and 0.306 eV for Ca. The specific capacities of Li, Na and Mg can reach up to 968, 613a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(27 citation statements)
references
References 62 publications
(64 reference statements)
2
25
0
Order By: Relevance
“…The phononic thermal conductivity was also predicted using the classical non-equilibrium molecular dynamics simulations. It is worthy to note that 2D materials and heterostructures owing to their good stability, desirable adsorption energy, remarkable ionic conductivity and high storage capacity have recently attracted remarkable attention for the application as active materials in rechargeable metal ion batteries [37][38][39][40][41][42][43][44][45] . We therefore also employed the DFT calculations to investigate the possible application of B-graphdiyne as an anode material for Li, Na, Mg and Ca ions storage.…”
Section: Introductionmentioning
confidence: 99%
“…The phononic thermal conductivity was also predicted using the classical non-equilibrium molecular dynamics simulations. It is worthy to note that 2D materials and heterostructures owing to their good stability, desirable adsorption energy, remarkable ionic conductivity and high storage capacity have recently attracted remarkable attention for the application as active materials in rechargeable metal ion batteries [37][38][39][40][41][42][43][44][45] . We therefore also employed the DFT calculations to investigate the possible application of B-graphdiyne as an anode material for Li, Na, Mg and Ca ions storage.…”
Section: Introductionmentioning
confidence: 99%
“…Even so, the E a with ∼0.30 eV for Ca−2D Ta 2 CS 2 can be comparable with that of the reported electrode of VO 2 . 57 Besides, the higher convergence criteria in CI-NEB calculations are adopted to examine the diffusion energy curves of the Ta 2 CS 2 −Li/Na system. It is found that the diffusion energy values would not be influenced by the higher convergence criteria but the fine structure of the curves in Figure S1.…”
Section: Resultsmentioning
confidence: 99%
“…Since the migration energy barrier is a key parameter that determines the charge and discharge rates of Mg-ion batteries [43,44] [45], borophene (0.97 eV) [46] and monolayer black phosphorus (0.09 eV). Although the value of 0.09 eV is already very small, it is still a bit larger than our minimum energy barrier value of 0.057 eV [47].…”
Section: Diffusion Energy Barriers Of Mg Atoms On Mo 2 Bmentioning
confidence: 99%